Accurate Pupil Features Extraction Based on New Projection Function - Mohammed, Ghassan J.; Hong, Bing Rong; Jarjes, Ann A. (Computing and Informatics, 2012)
Accurate pupil features extraction is a key step for iris recognition. In this paper, we propose a new algorithm to extract pupil features precisely within gray level iris images. The angular integral projection function (AIPF) is developed as a general function to perform integral projection along angular directions, both the well known vertical and horizontal integral projection functions can be viewed as special cases of AIPF. Another implementation for AIPF based on localized Radon transform is also presented. First, the approximate position of pupil center is detected. Then, a set of pupil's radial boundary points are detected using AIPF. Finally, a circle to the detected boundary points is fitted. Experimental results on 2655 iris images from CASIA V3.0 show high accuracy with rapid execution time.